Viscous cosmological models with particle creation in Brans-Dicke theory - Singh G.P.; Deshpande R.V.; Singh T. (My University, 2025)
The effect of bulk viscosity on the evolution of the spatially flat Friedmann-Robertson-Walker models in the context of open thermodynamical systems, which allow particle creation, is analyzed within the framework of Brans-Dicke theory. Particle creation and bulk viscosity have been considered as separated irreversible processes. To accommodate the viscous pressure and creation pressure, which is associated with creation of matter out of gravitational field, the energy-momentum tensor is modified. Dynamical behaviour of the models have been discussed.